مشروعيّة دليل العرف وصلاحيّته لمستجدّات العصر: دراسة في قضايا العادات الجديدة في ظلّ جائحة كوفيد- 19 - Mualimin Mochammad Sahid; Fettane Amar; Syed Mohammad Chaedar Syed Abdurrahman Al Yahya (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.